IRRIGAÇÃO E ADUBAÇÃO NITROGENADA NA CULTURA DO FEIJOEIRO, EM AQUIDAUANA-MS - CARDOSO, Kaio Roberto Conceição; LOPES, Adriano da Silva; PACHECO, Arthur; MOTA, Geovani Rocha; LOUREIRO, Lucas Areco; AMORIM, Andreza Cristina dos Santos (ANAIS DO ENIC, 2018)
-